2012
DOI: 10.1021/jp306290w
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Assembly of Gold Nanoparticle Arrays Covalently Attached to Silicon Surface Assisted by Localized Plasmon in the Nanoparticles

Abstract: It is essential to immobilize gold nanoparticles (AuNPs) firmly onto a certain substrate in a closely packed manner to apply plasmonic functions of AuNP in photonic/electronic devices. AuNP-Si systems are of particular interest for the integration of plasmonics to semiconductor electronics. Here we report on the arrangement of AuNPs into a 2-D array that was covalently bonded to a Si substrate without surface oxide. This process was achieved by simply irradiating visible light to a hydogen-terminated Si substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…[3][4][5] The lack of a silicon dioxide (SiO 2 ) interfacial layer 6,7 enables electron transmission to the substrate via SAMs. 16 Recent studies on the photoirradiation of both polymers and SAMs indicated that irradiation by vacuum ultraviolet (VUV) light of shorter wavelength (172 nm) in the presence of oxygen is a powerful technique for the functionalization of the terminal groups. 4,8 Several methods were reported for the preparation of alkyl-SAMs on a hydrogenterminated silicon (H-Si) substrate by heat, [9][10][11] ultraviolet (UV) exposure, 6,[12][13][14] visible (Vis) light exposure 6,15 and localized surface plasmons.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The lack of a silicon dioxide (SiO 2 ) interfacial layer 6,7 enables electron transmission to the substrate via SAMs. 16 Recent studies on the photoirradiation of both polymers and SAMs indicated that irradiation by vacuum ultraviolet (VUV) light of shorter wavelength (172 nm) in the presence of oxygen is a powerful technique for the functionalization of the terminal groups. 4,8 Several methods were reported for the preparation of alkyl-SAMs on a hydrogenterminated silicon (H-Si) substrate by heat, [9][10][11] ultraviolet (UV) exposure, 6,[12][13][14] visible (Vis) light exposure 6,15 and localized surface plasmons.…”
Section: Introductionmentioning
confidence: 99%
“…For photo‐initiated hydrosilylation reactions, four mechanisms have been proposed: [ 41 ] i) Si H bond homolysis followed by a radical reaction as described above, [ 51 ] ii) photoemission: photo induced electron emission followed by a nucleophilic attack on the positively charged silicon and hydrogen migration, [ 52 ] iii) plasmon‐mediated, [ 53 ] and iv) exciton‐mediated initiation: [ 45 ] a valence band electron is excited to the conduction band and is stabilized through coulomb interaction with the formed electron hole in the valence band.…”
Section: Grafting Organic Molecules To H Passivated Siliconmentioning
confidence: 99%
“…~20 nm diameter gold nanoparticles functionalized with terminal alkene groups preferentially underwent hydrosilylation and concomitant attachment to a silicon surface when illuminated with light that matched to the absorption maximum of the LSPR of the gold. 14 They proposed a mechanism that invoked a direct transfer of the energy of the photon absorbed by the LSPR to drive the hydrosilylation reaction. The wavelengths of green light centred around 520 nm would normally be of insufficient energy to promote hydrosilylation on a flat silicon surface, 15 pointing to the necessity of the LSPR of the nearby gold nanoparticle.…”
Section: Introductionmentioning
confidence: 99%